Características psicométricas de la batería de aptitudes BADYG-S renovado en estudiantes de Bachillerato peruano. Investigación de cátedra - Altez Rodríguez, Irma (2000)
The psychometric characteristics of the renovated Badyg-S is presented in a sample of 492 students of high school in Metropolitan Lima. Constructed validity of the test was verified by factorial analysis with varimax rotation. Constructs refers to General Intelligence and Logical Reasoning after the first 6 and 3 sub test respectively. Cronbach reliability coefficient (alpha) goes from 0.69 a to 0.95 in the different sub test. A scale is presented based on percentiles, when normality not being verified the sub test. However, the test results statistical different between sex although, as it will be explained this is a preliminary result.